Corn Response to Long‐Term Applications of Cattle Manure, Swine Effluent, and Inorganic Nitrogen Fertilizer. (1st September 2015) - Schlegel, Alan J.; Assefa, Yared; Bond, H. Dewayne; Wetter, Scott M.; Stone, Loyd R.
Abstract : Cattle ( Bos taurus ) manure and swine ( Sus scrofa ) effluent are applied to cropland to recycle nutrients, build soil quality, and increase crop productivity. The objective of this study was to determine the long‐term effects of land application of cattle manure and swine effluent using the Kansas Nutrient Utilization Plan on crop yield, yield components, and crop nutrient uptake. The study was conducted for 10 yr (1999 through 2008) near Tribune, KS. There were 10 treatments: three levels of cattle manure and swine effluent (P, N, and 2N), three levels of N fertilizer (N1 = 56, N2 = 112, and N3 = 168 kg N ha −1 ), and an untreated control. Corn ( Zea mays L.) grain and stover yields, yield components, and water use were measured. In all but 2 yr, all treatments significantly increased grain yield compared with the control and the lowest inorganic N rate. Mean corn grain yield over the years from the Cattle N and P, Swine N and P, and inorganic N2 and N3 treatments were about 2X, 1.8X, and 1.9X greater than the untreated control, respectively. Grain nutrient content and water productivity were consistently higher for the cattle manure treatments and the inorganic N2 and N3 treatments. However, grain yield and nutrient uptake did not differ among rates of cattle manure and swine effluent application. We concluded that using the lower application rate based on either N or P from the Kansas Nutrient Utilization Plan was sufficient to achieve optimal crop yield and water productivity.